1992
DOI: 10.1126/science.1589763
|View full text |Cite
|
Sign up to set email alerts
|

The role of crystal polarity in alpha-amino acid crystals for induced nucleation of ice

Abstract: The hydrophobic faces of single crystals of a series of pairs of racemic and chiral-resolved hydrophobic alpha-amino acids were used as a substrate, onto which water vapor has been cooled to freezing. The morphologies and molecular packing arrangements within each crystal pair are similar but only one of each pair exhibits a polar axis, parallel to the hydrophobic face exposed to water. Those crystals that have a polar axis induce a freezing point higher by 4 degrees to 5 degrees C than the corresponding cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
100
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 36 publications
7
100
1
1
Order By: Relevance
“…The effect of the electric field is to raise the temperature at which nucleation occurs (relative to a similar crystal with no electric field present) by the amount W/AS, or 20 to 50C. This is consistent with the results in (1). A plot of the shift in the nucleation temperature against &2 for all of the crystals that were tested by Gavish et al would reveal any correlation between these two properties.…”
Section: Technical Comments __supporting
confidence: 74%
See 2 more Smart Citations
“…The effect of the electric field is to raise the temperature at which nucleation occurs (relative to a similar crystal with no electric field present) by the amount W/AS, or 20 to 50C. This is consistent with the results in (1). A plot of the shift in the nucleation temperature against &2 for all of the crystals that were tested by Gavish et al would reveal any correlation between these two properties.…”
Section: Technical Comments __supporting
confidence: 74%
“…Such a proton-ordered water polar bilayer is part of the complex compound 3AgI NH4 6H20, as reported by B. L. Davis et al (1), who studied it in order to understand the exceptional ice-nucleating ability of aerosols obtained from AgI-NH4-acetone solution. Each ice-like water bilayer is sandwiched between a layer of Ag and one of I ions, and so must be protonordered and polar in a direction normal to the layer, although the H-positions have not been determined.…”
Section: Technical Comments __mentioning
confidence: 75%
See 1 more Smart Citation
“…Electric fields are often encountered in water near the surface of particles, molecules, and ions; they might play an important role in the heterogeneous nucleation of ice by impurity particles 9,14,21,27 .…”
Section: (V)mentioning
confidence: 99%
“…Experimentally, electrically-induced freezing, or an enhanced tendency to nucleate ice, were claimed to be observed at the electrostatically-charged surfaces of conductors 12,15,16,35 , polar amino acid crystals 14 , and pyroelectric crystals 21 . Water freezing experiments carried on charged surfaces suggested that electric fields much smaller than the predictions of simulations influence the nucleation of ice; nevertheless, careful freezing experiments carried under external electric fields [11][12][13]20 did not observe any effects of the electric field on the nucleation of ice.…”
Section: (V)mentioning
confidence: 99%